Estudo comparativo entre os tratamentos: laser de baixa intensidade, agente antifúngico e terapia fotodinâmica em onicomicoses - Pinto, Michael Vale (2014)
Introduction: Onychomycosis is a fungal disease that affects the nails. In photodynamic therapy (PDT), the laser light is associated with a photosensitizing agent and molecular oxygen, triggering a specific phenomenon in the photo-oxidation of various cell types jail. Objective: Studying the effects of the application of PDT, Low Level Therapy and antifungal therapies in the treatment of onychomycosis. Methodology: A prospective, randomized, controlled study was conducted with 28 patients in an institution in São Paulo, where treatments were evaluated: topical antifungal, Laseterapia and PDT. Results: The antifungal therapies based and Low Level Therapy showed no clinical improvement with the treatment. The basis of PDT treatment had clinical improvement. Conclusions: The use of PDT may form themselves into new effective, safe and inexpensive therapeutic tool, serving as a possible treatment. However, it is necessary to conduct longitudinal studies of the next steps with larger samples.